BS ISO 4586-3. High-pressure decorative laminates (HPL, HPDL). Sheets based on thermosetting resins (usually called laminates). Part 3. Classification and specifications for laminates less than 2 mm thick and intended for bonding to supporting substrates (10th March 2020) - British Standards Institution
No abstract available